An eco-efficiency analysis of the snowboard manufacturing industry. (12th October 2009) - Walsh, Justin M.; Singh, Gangaram
This paper examines the eco-efficiency of the snowboard manufacturing industry and how it relates to global warming, increasing climactic volatility and reductions in snowfall worldwide. Our data, and subsequent analysis, illustrate the current eco-efficiency activity within a sample group of snowboard brands headquartered throughout North America and Europe. Though the sample group exhibited an overall eco-efficiency activity level of 'informed', the primary data show an industry wide need for standardisation and implementation of comprehensive environmental management systems and all-encompassing life-cycle assessments. With the ultimate goal of industry wide sustainable development and cradle-to-cradle design, we conclude with a list of current and prospective best practices throughout the global snow sports industry.